Ukrainian Greek Catholic Church in the second half of the 20th century: the analysis of modern historiography - Пшеничний, Тарас Юрійович (Київський національний університет імені Тараса Шевченка, 2018)
Ukrainian Church History is a great field for scientific research. The 20th century was a kind of test for the survival and self-determination of Ukrainian churches. Through the spread of general pressure on the Ukrainian national movement, a repression mechanism was introduced against the Institute of the Church as an integral part of the social life of Ukrainian people in the Soviet Union. A characteristic feature of the anti-church campaign in the Ukrainian SSR was the introduction of a "new" model of social relations, built on the principles of atheism and godlessness. The only legal national church until March 1946, which opposed this path, was the Ukrainian Greek Catholic Church. In the second half of the 20th century its clergy, while in an unlawful position in the USSR, remained in the center of the Ukrainian resistance movement against the Soviet system. The article presents the modern view of domestic and foreign scholars on the history of the Ukrainian Greek Catholic Church in the second half of the 20th century. On the basis of a broad historiographic base, an attempt was made to show the place of the UGCC in the Ukrainian national movement, its influence on the democratization of social processes in the second half of the 1980s, and others. Thanks to the works of foreign historians, the relevance of church issues in the study of socio-political processes in the USSR is shown. According to some scholars, ignoring this it is impossible to understand the phenomenon of the national movement itself, including in the western regions of the Ukrainian SSR.

Українська церковна історія – це масштабне поле для наукового пізнання. ХХ ст. стало своєрідним тестом на виживання та самовизначення для українських церков. Через тотальний утиск у Радянському Союзі українського національного руху, механізм репресій було запущено і проти інституту церкви як невід'ємної складової суспільного життя українського народу. Характерною рисою антицерковної кампанії в УРСР стало насадження "нових" моделей суспільних відносин, побудованих на засадах атеїзму й безбожництва. Єдиною легальною національною церквою до березня 1946 р., яка всіляко чинили цьому опір, була Українська греко-католицька церква. Протягом усієї другої половини ХХ ст. її духовенство й чернецтво, перебуваючи в нелегальному становищі, залишалося центром, навколо якого консолідувався український рух опору. Представлено сучасний погляд вітчизняних і зарубіжних учених на історію Української греко-католицької церкви у другій половині ХХ ст. На основі широкої історіографічної бази здійснено спробу показати місце УГКЦ в українському національному русі, її вплив на демократизацію суспільних процесів у другій половині 1980-х рр. тощо. Завдяки працям зарубіжних істориків вдалося показати актуальність церковної проблематики при вивченні суспільно-політичних процесів у СРСР. Її ігнорування, як відзначають окремі вчені, не дозволяє збагнути самого феномену національного руху, у тому числі в західних областях Української РСР.
Українська греко-католицька церква у другій половині ХХ століття: історіографічний аналіз
Keywords: UGCC; ideology; atheism; Ukrainian SSR; USSR; historiography; УГКЦ; ідеологія; атеїзм; УРСР; СРСР; історіографія